(untitled) (Research, Society and Development, 2021)
Bovine papilomavírus (BPVs) is the etiological agent of bovine papillomatosis, a disease that triggers warts throughout the skin, udder, roofs, genitalia and in more severe cases can develop extensive papillomas, cause neoplasia in the digestive tract and bladder, cause losses in productivity and losses to livestock. In Brazil, the occurrence of BPV infection is relatively common, but the identification of viral types is still sporadic. The present study is a research report that aimed to describe the occurrence of BPV infections in dairy cattle affected by papillomatosis, based on the nucleotide sequences of the ORF L1, the most conserved sequence. Twenty-five samples of cutaneous wart from nine cattle clinically diagnosed as cutaneous papillomatosis were analyzed in the state of Goiás, central-western Brazil. Amplification was obtained in 11 samples (papilloma) from different cattle. PCR reactions followed by sequencing revealed the presence of BPV-1 in 60%, BPV-5 in 40%, and BPV-14 in 20% of the samples analyzed. The presence of coinfection was verified in 60% of the amplified samples. These data suggest that several types of BPV can infect a lesion simultaneously and demonstrate the possibility that BPV infection in epithelial tissue can occur without restriction to one or two viral types, demonstrating the region’s genetic diversity. As far as we know, this is the first registry of typification of BPVs of the central-western region of Brazil. This analysis provides important information for bovine papillomavirus (BPV) research in Brazil.